2005
DOI: 10.1021/la047916u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsed Low-Frequency Electromagnetic Fields on Water Characterized by Light Scattering Techniques:  Role of Bubbles

Abstract: Well-characterized purified water was exposed for 6 h to pulsed low-frequency weak electromagnetic fields. After various time periods, nondegassed and degassed water samples were analyzed by static light scattering. Just after electromagnetic exposure (day 0), a reduction of over 20% in the maximum light scattering intensity at 488 nm wavelength in both nondegassed and degassed samples was observed. By contrast, on day 12 the difference was observed only in nondegassed water samples. The latter effect was attr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
1
25
0
2
Order By: Relevance
“…The average hydrogen nanobubble diameter, as revealed by DLS, was reported to decrease from 600 to 200 nm with increasing current density reported in a previous paper [7]. Vallee et al found that the stability of nanobubbles with a diameter of around 300 nm that was established during the water purification process was affected by electromagnetic exposure presumably because the exposure disturbed the ionic double layer [23]. Bunkin et al indicated that nanobubbles obtained by cavitation of bubbles were stabilized by the adsorption of negative ions on the interface; the lifetime of the nanobubbles was 10 h in open air [24].…”
Section: Introductionmentioning
confidence: 74%
“…The average hydrogen nanobubble diameter, as revealed by DLS, was reported to decrease from 600 to 200 nm with increasing current density reported in a previous paper [7]. Vallee et al found that the stability of nanobubbles with a diameter of around 300 nm that was established during the water purification process was affected by electromagnetic exposure presumably because the exposure disturbed the ionic double layer [23]. Bunkin et al indicated that nanobubbles obtained by cavitation of bubbles were stabilized by the adsorption of negative ions on the interface; the lifetime of the nanobubbles was 10 h in open air [24].…”
Section: Introductionmentioning
confidence: 74%
“…Consequently, the distribution of water molecules would be modified and, therefore, also the physical and chemical properties of the magnetized water. By contrast, experiments by Colic and Morse () and by Vallée and others (,b) suggest that the gas bubble/water interface is the primary target of the MF action because no MF effects are observed when water is degassed. According to these authors, MF exposition leads to the destabilization of the air nanobubbles, naturally present in non‐degassed water, by disturbing the ionic balance between the negative ions adsorbed on the bubbles and the shell of counter ions.…”
Section: Effects Of Mfs On Watermentioning
confidence: 87%
“…The bubbles widely vary in size from millimeters, whose contribution to the backscattering signal noticeably decreases with time, to nanometers [9,10] or thermodynamically equilibrium cavities [11], which live in water for hours [12].…”
Section: Resultsmentioning
confidence: 99%